Characterization, Avoidance and Repair of Packet Collisions in Inter-Vehicle Communication Networks - Mittag, Jens (KIT Scientific Publishing, 2012)
This work proposes a combined and accurate simulation of wireless channel, physical layer and networking aspects in order to bridge the gaps between the corresponding research communities. The resulting high fidelity simulations enable performance optimizations across multiple layers, and are used in the second part of this thesis to evaluate the impact of fast-fading channel characteristics on Carrier-Sense Multiple Access, and to quantify the benefit of successive interference cancellation.